Holistic Localised Performance Assessment for Agroecology (HOLPA) - Stats4SD; Sanchez Bogado, Andrea Cecilia; Jones, Sarah (2025)
Interface providing step-by-step training on setting up, using, analyzing and visualizing results from Holistic Localised Performance Assessment for Agroecology (HOLPA) farm-household and field surveys.